Aldosterone- and Cortisol Co-secreting Adrenal Cortical Neoplasm With Lipomatous and Myelolipomatous Metaplasia . Issue 2 (21st February 2023) - Jinna, Sruthi; Taftaf, Rokana; Petros, Firas G; Jun, John Y
Abstract: We report a case of a 58-year-old woman with a history of hypertension diagnosed at aged 35 years, on 5 antihypertensive agents and a history of intermittent spontaneous hypokalemia, was found to have a 6-cm left adrenal mass on computed tomography scan of the abdomen. The unenhanced computed tomography attenuation of the adrenal mass was −16 Hounsfield units (HU). The biochemical evaluation showed potassium of 2.8 mEq/L (SI unit, mmol/L) (reference range, 3.5-5.0), plasma aldosterone concentration of 61.3 ng/dL (SI unit, 1701 pmol/L) with plasma renin activity of 0.4 ng/mL/h (SI unit, μg/L/h). An overnight 1-mg dexamethasone suppression test showed nonsuppressible serum cortisol of 10.8 μg/dL (SI unit, 298 nmol/L). Dehydroepiandrosterone sulfate and ACTH were measured at 24.5 μg/dL (age-adjusted, 26-200) (SI unit, 0.66 μmol/L; 0.70-5.43) and <5 pg/mL (SI unit, < 1.1 pmol/L), respectively. Left adrenalectomy was performed and hydrocortisone therapy was initiated. Postoperatively and thereafter, her blood pressure was controlled with no antihypertensive agent. Seven months later, hydrocortisone therapy was stopped once her cortisol level had normalized. Pathology showed adrenal cortical neoplasm of uncertain malignant potential with associated lipomatous and myelolipomatous metaplasia. This is a rare case of aldosterone and cortisol co-secreting adrenal cortical neoplasm of uncertain malignant potential with lipomatous and myelolipomatous metaplasia. Although the majority of cases of myelolipoma are benign and nonfunctioning, this case emphasizes the importance of thorough hormonal and morphologic evaluation of the tumor.